CREACIÓN DE REPUTACIÓN CORPORATIVA MEDIANTE LA ADECUADA GESTIÓN DE LA RESPONSABILIDAD SOCIAL. ESTUDIO DEL CASO DE LAS EMPRESAS: BCP, KIMBERLY CLARK Y AFP INTEGRA-SURA - Lozano, Julianna Paola Ramírez (European Scientific Journal, ESJ, 2015)
Social responsibility is a voluntary and ethic manifestation that should be understand as a philosophy of work groups and a role model of how organizations should act in relationships between them and their stakeholders. The article is about the case study of three companies: Banco de Crédito del Perú (BCP), Kimberly Clark Perú and AFP Integra-SURA. In the analysis we get to know that the element of social responsibility plays is a very important part in the construction of corporate reputation, been one of the most visual elements, not the only one, but certainly one of the most important ones. Social responsibility guaranties and allows good relationships with the stakeholders, who are the ones that determine the corporate reputation of the company.